The celestine vision living the new spiritual awareness - Redfield, James (London Bantam Press, a division of Transworld Publishers Ltd, 1997)
Redfield, "discusses for the first time the historical and scientific background," of the planetary awakening described in his first two books.
Includes bibliographical references (pages 235-242)
Keywords: Spiritual life; Conduct of life; Self-realization.; Millennialism